Folic Acid-Conjugated Silica-Modified TbPO4·H2O Nanorods for Biomedical Applications. (28th October 2021) - Vinh, Le Thi; Huong, Tran Thu; Phuong, Ha Thi; Khuyen, Hoang Thi; Hung, Nguyen Manh; Thao, Do Thi; Minh, Le Quoc
Abstract : We report on the synthesis and characterization of folic acid-conjugated silica-modified TbPO4 ·H2 O nanorods for biomedical applications. The uniform shape TbPO4 ·H2 O nanorods with a hexagonal phase were successfully synthesized by wet chemical methods. A novel TbPO4 ·H2 O@silica-NH2 nanocomplex was then formed by functionalizing these nanorods with silica and conjugating with biological agents. The field emission scanning electron microscopy, energy-dispersive X-ray, and X-ray diffraction reveal the morphology and structure of the nanorods, with their controllable sizes (500-800 nm in length and 50-80 nm in diameter). The Fourier transform infrared spectroscopy was employed to identify chemical substances or functional groups of the TbPO4 ·H2 O@silica-NH2 nanocomplex. The photoluminescence spectra show the four emission lines of TbPO4 ·H2 O@silica-NH2 in folic acid at 488, 540, 585, and 621 nm under 355 nm laser excitation, which could be attributed to the 5 D4 - 7 F j (J = 6, 5, 4, 3 ) transitions of Tb 3+ . The TbPO4 ·H2 O@silica-NH2 nanorods were conjugated with folic acid for the detection of MCF7 breast cancer cells. The obtained results show a promising possibility for the recognition of living cells that is of crucial importance in biolabeling.